Characterization of heavy metal contamination in wetland sediments of Bosten lake and evaluation of potential ecological risk, China - Wang, Kai; Aji, Dilinuer; Li, Pingping; Hu, Congqiao (Frontiers in Environmental Science, 2024)
In November 2023, twenty-two sediment samples were collected from the Bosten Lake wetland in Xinjiang to determine the concentrations of eight heavy metals: arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb), and zinc (Zn). This data was used to assess heavy metal contamination and potential ecological risks in the sediments using the Pollution Load Index (PLI) and the Potential Ecological Risk Index (RI). Additionally, multivariate statistical analysis and Positive Matrix Factorization (PMF) were employed to elucidate potential sources and their contributions to contamination. The following are the main conclusions: (1) average concentrations of Zn, Cd, Cr, Pb, and Hg in the sediments surpassed Xinjiang soil background levels by factors of 1.01, 3.58, 1.32, 1.94, and 1.53, respectively. (2) Sediments demonstrated severe pollution with Cd, slight pollution with Zn, Cr, Pb, and Hg, while Cu and Ni indicated mild pollution and As showed non-polluted levels. The overall PLI average (1.01) suggested slight contamination.(3) The descending order of average single ecological risk values were Cd, Hg, Pb, Cu, Ni, Cr, As, and Zn, with a comprehensive RI averaging at 184.07, signaling a moderate ecological risk. (4) Source apportionment revealed that Zn, Cu, Pb, and Ni were influenced by transportation and household waste emissions, while Cr and As were dictated by natural background levels. Hg predominately originated from fossil fuel combustion and Cd from agricultural activities. (5) Mixed sources accounted for the following percentage contributions to sediment heavy metal content: transportation and domestic waste (30.41%), natural background (25.88%), fossil fuel combustion (22.40%), and agricultural activities (21.31%). With anthropogenic inputs exceeding those of natural origins, it is imperative to prioritize the management of Cd, Hg, and Pb as primary pollutants within the region.